Estimation of gasdynamic compressor stability characteristics of turbojet engine in operation - Ратинський, В. В. (Proceedings of National Aviation University (archive), 1998)
Considered is the method of evaluation of gas dynamic stability of compressors in operation. The method is based on the determination of position of operating rating curve on curves of compressors taking into consideration conditions of joint work units of gas turbine engine. Given are results of numeric experiment for three-shaft two-flow turbojet engine D-36 on PC